Adjunctive dexamethasone therapy in unconfirmed bacterial meningitis in resource limited settings: is it a risk worth taking?. Issue 1 (December 2016) - Gudina, Esayas; Tesfaye, Markos; Adane, Aynishet; Lemma, Kinfe; Shibiru, Tamiru; Wieser, Andreas; Pfister, Hans-Walter; Klein, Matthias
Abstract Background Bacterial meningitis is associated with significant morbidity and mortality despite advances in medical care. The main objective of this study was to assess the association of adjunctive dexamethasone treatment with discharge outcome of patients treated as bacterial meningitis in low income setting. Methods A retrospective study was conducted at four teaching hospitals across Ethiopia. Patients of age 14 years and older treated as cases of bacterial meningitis between January 1, 2011 and April 30, 2015 were included in this study. Information regarding sociodemographic data, clinical presentations, laboratory data, treatments given and status at hospital discharge were retrieved from patients' medical records using a structured questionnaire. Predefined outcome variables at discharge were analysed using descriptive statistics. Multivariable logistic regression was used to identify factors independently associated with poor outcome. Results A total of 425 patients treated with the presumptive clinical diagnosis of bacterial meningitis were included in this study (lumbar puncture done in 56 %; only 19 % had CSF findings compatible with bacterial meningitis, and only 3 % had proven etiology). The overall in hospital mortality rate was 20.2 %. Impaired consciousness, aspiration pneumonia, and cranial nerve palsy at admission were independently associated with increased mortality. Adjuvant dexamethasone, which was used in 50.4 % of patients, was associated with increased in-hospital mortality (AOR = 3.38; 95 % CI 1.87–6.12, p < 0.001) and low Glasgow outcome scale (GOS) at discharge (AOR = 4.46 (95 % CI 1.98–10.08). This association between dexamethasone and unfavorable outcome was found to be more pronounced in suspected but unproven cases and in those without CSF alterations compatible with bacterial meningitis. Conclusion Most patients treated for suspected bacterial meningitis did not receive proper diagnostic workup. Adjuvant dexamethasone use in clinically suspected but unproven cases of bacterial meningitis was associated with an increased mortality and poor discharge GOS. These findings show that there are potential deleterious effects in unconfirmed cases in this setting. Physicians practising under such circumstances should thus abide with the current recommendation and defer the use of adjuvant corticosteroid in suspected cases of bacterial meningitis.